Predictors of Shock‐Reduction Programming and Its Impact on Implantable Cardioverter‐Defibrillator Therapies and Mortality: The CERTITUDE Registry - Sebastian E. Beyer; Camden Harrell; Steven Mullane; Valentina Kutyifa; Malini Madhavan; Jonathan P. Piccini; Gaurav A. Upadhyay; James E. Ip; George Thomas; Christopher F. Liu; Steven M. Markowitz; David Hayes; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Shock‐reduction implantable cardioverter‐defibrillator programming (SRP) was associated with fewer therapies and improved survival in randomized controlled trials, but real‐world studies investigating SRP and associated outcomes are limited. Methods and Results The BIOTRONIK CERTITUDE registry was linked with the Medicare database. We included all patients with an implantable cardioverter‐defibrillator implanted between August 22, 2012 and September 30, 2021 in the United States. SRP was defined as programming to either a therapy rate cutoff ≥188 beats per minute or number of intervals to detection ≥30/40 for treatment. Among 6781 patients (mean 74±9 years; 27% women), 3393 (50%) had SRP. Older age, secondary prevention indication, and device implantation in the southern or western United States were associated with lower use of SRP. The cumulative incidence rate of implantable cardioverter‐defibrillator shocks was lower in the SRP group (5.1% shocks/patient year) compared with the non‐SRP group (7.2% shocks/patient year) (adjusted hazard ratio [HR], 0.83 [95% CI, 0.73–0.96]; P=0.005). Over a median follow‐up of 2.9 years, 739 deaths occurred in the SRP group and 822 deaths occurred in the non‐SRP group (adjusted HR, 0.97 [95% CI, 0.88–1.07]; P=0.569). SRP was associated with a lower all‐cause mortality among patients without ischemic heart disease compared with patients with ischemic heart disease (adjusted HR, 0.64 [95% CI, 0.48–0.87] versus adjusted HR, 1.02 [95% CI, 0.92–1.14]; Pinteraction=0.004). Conclusions Adoption of SRP is low in real‐world clinical practice. Age, clinical variables, and geographic factors are associated with use of SRP. In this study, SRP‐associated decrease in mortality was limited to patients without ischemic heart disease.